Synthesis and Evaluation of Protein–Phenylboronic Acid Conjugates as Lectin Mimetics - Whited, Joshua (ACS Omega, 2018)
[Image: see text] Glycan-binding molecules, such as lectins, are very important tools for characterizing, imaging, or targeting glycans and are often involved in either physiological or pathological processes. However, their availability is far less compared to the diversity of native glycans. Therefore, development of lectin mimetics with desired specificity and affinity is in high demand. Boronic acid reacts with 1,2- and 1,3-diols of saccharides in aqueous media through reversible boronate ester formation and are regarded as synthetic lectin mimetics. In this study, bovine serum albumin (BSA)–phenylboronic acid (PBA) conjugates were synthesized in a density-controlled manner by targeting both aspartic and glutamic acids to afford lectin mimetics with multivalent PBA, as multivalency is a key factor for glycan recognition in both specificity and affinity. The resultant BSA–PBA conjugates were characterized by sodium dodecyl sulfate polyacrylamide gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry analysis. Their macrophage cell surface glycan-binding capacity was characterized by a competitive lectin-binding assay examined by flow cytometry, and 3-(4,5-di-methylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed biocompatibility. These novel lectin mimetics will find a broad range of applications as they can be wittingly modified, altering binding specificity and capacity.